Bow‐tie diagrams in downstream hazard identification and risk assessment. Issue 1 (4th May 2013) - Saud, Yaneira E.; Israni, Kumar (Chris); Goddard, Jeremy
<x xml:space="preserve">Abstract</x> Bow‐tie diagrams are emerging as a very useful tool to depict and maintain an up‐to‐date, real‐time, working risk management system embedded in daily operations. They are a proven concept in the worldwide offshore industry. These diagrams provide a pictorial representation of the risk assessment process. This article introduces the bow‐tie concept to the downstream and chemical process industries in the United States. The authors believe that bow‐tie diagrams can be a resourceful method in the safety and risk practitioner's toolkit to improve performance of the hazard identification and risk assessment process and to demonstrate that major hazards are identified and managed to as low as reasonably practicable. Because of their graphical nature, the biggest advantage of bow‐tie diagrams is the ease to understanding of risk management by upper management and operations groups. © 2013 American Institute of Chemical Engineers Process Saf Prog, 33: 26–35, 2014